Accurate 16S Absolute Quantification Sequencing Revealed Vaginal Microecological Composition and Dynamics During Mixed Vaginitis Treatment With Fufang FuRong Effervescent Suppository - Li, Meng; Zeng, Zhen; Feng, Huijun; Cao, Yang; Zhang, Qiongqiong; Lv, Tao; Yang, Xingsheng; Song, Dianrong; Li, Ping; Hu, Lina; Fan, Shangrong; An, Ruifang; et al. (Frontiers in cellular and infection microbiology, 2022)
The diagnosis and treatment of mixed vaginitis are more complicated than single pathogenic infections, and there may be adverse reactions and several contraindications to conventional antibiotic therapy. Therefore, this study aimed to evaluate the preliminary effects of Fufang Furong Effervescent Suppository for the management of aerobic vaginitis (AV) mixed with bacterial vaginosis (BV) using Accurate 16S absolute quantification sequencing (Accu16S). In the present randomized, blind, multi-center clinical trial, women (20 to 55 years) who had received a diagnosis of AV+BV were randomly assigned into clindamycin positive control (n = 41) and Fufang Furong Effervescent Suppository (n = 39) groups. The follow-up occurred in three time periods (V1: -2~0 days; V2: 15-17 days; V3: 40 ± 3 days). At each visit, two vaginal swabs, one for clinical evaluation and one for laboratory examination, were taken from each patient. The Nugent score, Donders' score, drug-related complications, recurrence rates, and microecological changes of vaginal swabs were assessed in the time three periods. At baseline, the two groups were similar in frequency of presentation with vaginal burning, odor, abnormal discharge, and itching. No meaningful differences in Nugent and Donders' scores were detected between the two groups at stage V2 (Nugent: = 0.67; Donders': 0.85) and V3 (Nugent: = 0.97; Donders: = 0.55). The Furong group presented fewer complications compared to the Clindamycin group. However, this difference was not statistically significant ( = 0.15). Additionally, Accu16S indicated that the total abundance of bacteria in both groups sharply decreased in stage V2, but slightly increased in V3. In stage V3, the absolute abundance of in the Furong group was considerably higher compared to untreated samples ( < 0.05). On the other hand, no momentous increase was detected in the Clindamycin group ( > 0.05). Fufang Furong Effervescent Suppository can be as effective as clindamycin cream in the management of AV+BV while may restore the vagina microecosystem better.